Avaliação do eixo hipotálamo-hipófise-adrenal em indivíduos com e sem mediunidade (experiência anômala) em um contexto religioso - Vencio, Sérgio Alberto Cunha (2017)
Objective - To evaluate the HPA axis and the mental health status in a non-pathological dissociation condition (mediumship) Methods - In this prospective and controlled study, 29 psychophonic mediums (group 1) were evaluated before and after psychophony and compared to 22 non-medium volunteers of the same religious context (group 2) before and after a creative visualization, simulating a mediumistic assistance. Plasma catecholamines, ACTH, cortisol and glucose were measured pre-and 1 hour after the intervention. A structured questionnaire - DDIS was applied (Dissociative Disorders Interview Schedule) and the results were compared with historical data from patients with dissociative disorder (DD) who answered the DDIS. Results - In group 1, cortisol and ACTH decreased (14.7 μg/dl to 11.2 μg/dl with p-0.001 and 20.6 pg/ml to 13.9 pg/ml with p-0.001, respectively), However, the HPA axis showed diversified responses with epinephrine and noradrenaline decreasing after the intervention (39 pg/ml at 33 pg/ml and 311.2 pg/ml at 284.1 pg/ml, respectively) and an increased in dopamine (41.7 pg/ml to 44.4 pg/ml with p-0.046). In group 2, cortisol decreased from 15.5 μg/dl to 13.4 μg/dl (p -0.01). The scores obtained in the structured interview (DDIS) were similar in both groups, but with considerable differences when compared with historical data from TD patients. Conclusion - This study showed that one hour after psychophony the HPA axis remains preserved in mediums. Dopamine is the main neurochemistry of religious manifestations and may eventually constitute a biomarker of this phenomenon.